Collaborative Confidence: Transforming Teacher Performance through Teamwork and Self-Efficacy - Abdullah Muzakar; Sitti Rohmi Djalilah; Muhamad Suhardi (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This study aims to comprehensively analyze the influence of teamwork and self-efficacy on teacher performance at a public junior high school in Jonggat District, Central Lombok Regency. Data were collected through participant observation and questionnaires using a Likert scale of 1-5. The method used was a survey with a correlational approach, while data analysis was carried out using descriptive and inferential statistics, including path analysis. The results of the study showed that (1) teamwork has a direct positive effect on teacher performance, with a correlation coefficient of 0.582 and a path coefficient of 0.412; (2) self-efficacy has a direct positive effect on teacher performance, with a correlation coefficient of 0.571 and a path coefficient of 0.392; and (3) teamwork also has a direct positive effect on self-efficacy, with correlation and path coefficients of 0.433 each. These findings confirm that improving teamwork can support the achievement of higher teacher performance, as well as strengthening teacher self-efficacy. This study recommends that schools prioritize the development of teamwork and improving teacher self-efficacy through training, professional development programs, and a collaborative work environment. The limitations of this study include the population being limited to junior high schools in Jonggat, so generalization of the results needs to be done with caution